Crystal Growth and Application of Rare Earth Perovskite Nickel Oxide Compounds by High Pressure Flux Method
By using a high-barometric flux method with an alkali flux system under lower temperature and oxygen pressure conditions, the problem of too small crystal size in the prior art was solved, and large-sized high-quality RNiO3 single crystals were successfully obtained, which is suitable for applications in a variety of cutting-edge research fields.
Patent Information
- Application Number
- CN202211337263.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-28
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2042-10-28
AI Technical Summary
In the prior art, when growing rare earth perovskite nickel oxide single crystals, the temperature and oxygen pressure are too high, resulting in too small crystal size, making it difficult to obtain large-sized high-quality single crystals.
The rare earth perovskite nickel-oxygen compound high-barometric flux method is used to grow crystals at lower temperatures and oxygen pressures by using an alkali flux system, which reduces the growth temperature and oxygen pressure, thereby obtaining a larger size of RNiO3 crystal.
Large-sized RNiO3 single crystals were successfully obtained under lower conditions, with crystal sizes up to 45-60μm and high crystal quality, which was suitable for further physical testing and applications.
Smart Images

Figure CN115787060B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the crystal growth and application of rare earth perovskite nickel oxide compounds by high-pressure flux method, and belongs to the technical field of crystal materials. Background Art
[0002] In 1911, the discovery of the superconducting properties of mercury opened up the research on superconducting materials. Superconducting materials discovered so far are mainly divided into conventional superconductors and unconventional superconductors. The origin of superconductivity in conventional superconductors can be perfectly explained by the BCS theory, while for unconventional superconductors such as copper-based and iron-based high-temperature superconductors, there is currently no unified and quantitative theoretical explanation for their superconductivity mechanism. At present, the key basic scientific issues in superconductivity research focus on the high-temperature superconductivity mechanism and the design and discovery of room-temperature superconductors. The discovery of new high-temperature superconductors will provide a new material platform and ideas for solving the global problem of high-temperature superconductivity mechanism.
[0003] In August 2019, Professor Hwang's research group at Stanford University successfully prepared Nd on SrTiO3 substrate using laser pulse deposition. 0.8 Sr 0.2 NiO2 thin film, and discovered the superconducting phenomenon with a critical transition temperature of 9-15K. 1-x Sr x NiO2(R=Nd,Pr,La),La 1-x Ca x NiO2 and Nd6Ni5O 12 Superconductivity has been found in thin films. However, no superconductivity has been found in polycrystalline materials, which may be due to poor sample quality. Due to the limited detection volume of thin films, tests such as neutron scattering cannot be performed, which seriously hinders the study of its superconducting mechanism. In addition, basic scientific issues related to nickel-based superconductivity research, such as what is the magnetic ground state of rare earth perovskites? Are there competing orders such as charge density waves and spin density waves? Does a pseudogap phase also exist above the superconducting phase temperature range? Strange metals? Single crystals are an ideal platform for solving the above key basic scientific problems and studying the anisotropic physical properties of nickel-based materials.
[0004] Monovalent nickel oxide is difficult to obtain directly through chemical reactions. Therefore, in order to prepare high-quality RNiO2 single crystals, high-quality RNiO3 parent phase single crystals must be prepared first. Therefore, the growth of RNiO3 single crystals is a difficult problem that needs to be overcome in studying the superconducting properties of low-valent nickel oxides. At present, there are two methods for synthesizing trivalent nickel parent phase single crystals, one is the high-pressure flux method, and the other is the high-pressure floating zone method. Both methods require a high oxygen pressure to stabilize the trivalent nickel ions, and as the radius of the rare earth ions decreases, the required oxygen pressure will continue to increase, which places high demands on the equipment. At present, the growth of RNiO3 single crystals with high pressure flux mostly uses chloride as a flux under high temperature and high isostatic pressure conditions, but it still cannot obtain large-sized RNiO3 single crystals. At present, there are literature reports that RNiO3 (R=Nd, Sm, Gd, Dy) with a size of 10-15μm was grown under 2000bar oxygen pressure and 1000℃ using chloride as a flux. Summary of the invention
[0005] In view of the shortcomings of the prior art, especially the technical defects that the existing growth temperature and pressure are too high and the obtained crystal size is too small, the present invention provides a rare earth perovskite nickel oxide compound high pressure flux method crystal growth and application. The present invention obtains a larger RNiO3 crystal under the condition of lowering the growth temperature and oxygen pressure by exploring a new flux system.
[0006] The technical solution of the present invention is as follows:
[0007] A rare earth perovskite nickel oxide compound high pressure flux method crystal growth method comprises the following steps:
[0008] Using NiO and R2O3 as raw materials, R is a rare earth element (R=Pr-Dy), an alkali flux system is used to fill with oxygen to carry out crystal growth. The temperature is first raised to 400-500°C to fully melt the raw materials, and then cooled to the growth temperature to allow the crystal to grow. The oxygen pressure range is 5-300 bar, and the growth temperature is 150-450°C. After the growth is completed, rare earth perovskite nickel oxide RNiO3 crystals are obtained.
[0009] The RNiO3 crystal prepared by the present invention has a metal-insulator phase transition, is metal at high temperature, belongs to the orthorhombic crystal system, has a space group of Pbnm, and the phase transition temperature increases with the decrease of the R ion radius. N There is antiferromagnetic order below. RNiO3 is the parent phase material for preparing low-valent nickel oxide compound RNiO2. The powder X-ray diffractometer data of the prepared RNiO3 crystal is consistent with the powder diffraction standard PDF card, indicating that the grown crystal RNiO3 crystal is confirmed to be a perovskite structure by single crystal analysis.
[0010] The size of the RNiO3 crystals prepared by the method of the present invention is greatly improved compared with the prior art, and the crystal size can reach 45-60 μm.
[0011] The RNiO3 crystal prepared by the present invention is black, rectangular, stable at room temperature, and has no decomposition and deliquescence. The growth cycle can be adjusted according to demand to obtain high-quality RNiO3 single crystals for physical testing.
[0012] The RNiO3 single crystal prepared by the present invention has a metal-insulator phase transition. For example, the metal-insulator phase transition of NdNiO3 occurs at about 160K.
[0013] According to the present invention, preferably, R=Nd, Sm, Gd or Dy.
[0014] According to the present invention, preferably, the alkaline flux is one of NaOH and KOH or a mixture of two or more thereof; when the flux is a NaOH-KOH mixed system, the molar ratio of NaOH-KOH is preferably 1:1.
[0015] According to the present invention, preferably, the mass ratio of the raw material to the flux is 0.15:(1-2).
[0016] According to the present invention, preferably, during the process of cooling to the growth temperature, the cooling rate is 15-0.4°C / h, more preferably 10-0.5°C / h.
[0017] According to the present invention, oxygen is continuously added during the growth process to maintain the oxygen partial pressure.
[0018] According to the present invention, preferably, the growth temperature is 170-360°C, and may be 200°C, 250°C, or 350°C; preferably, the oxygen pressure ranges from 5-270bar, and may be 80bar, 90bar, 100bar, 110bar, 200bar, 240bar, 260bar, or 300bar.
[0019] According to the present invention, preferably, the growth period of the RNiO3 crystal is 3-12 days.
[0020] According to the present invention, preferably, the growth conditions of RNiO3 crystals are: cooling to 250-200°C at a rate of 0.5-10°C / h, and the growth period is 3-12 days.
[0021] According to the present invention, a rare earth perovskite nickel oxide compound high pressure flux method crystal growth method, a preferred embodiment, comprises the following steps:
[0022] (1) NiO, R2O3, R is a rare earth element, are mixed in a stoichiometric ratio, pressed into tablets, added to a prepared flux system, mixed evenly, and obtained a crystal growth material;
[0023] The flux is: NaOH-KOH, wherein the molar ratio of NaOH to KOH is (0-1):1;
[0024] The mass ratio of the raw material to the flux is 0.15:(1-2);
[0025] (2) placing the crystal growth material obtained in step (1) into a platinum crucible, filling it with oxygen, adjusting the pressure, heating it to 400-500° C., maintaining the temperature to fully melt the raw material, and then cooling it to allow the crystal to grow, thereby obtaining a rare earth perovskite nickel oxide RNiO3 crystal;
[0026] The crystal growth temperature range is 170-400° C., the oxygen pressure range is 5-300 bar, and the cooling rate is 10-0.5° C. / h.
[0027] In the above-mentioned crystal growth process of the present invention, the chemical reaction formula involved is: R2O3+2NiO+0.5O2→2RNiO3.
[0028] According to the present invention, the coupling effect between lattice-charge-spin-orbit in the perovskite nickel oxide compound RNiO3 crystal makes it have the potential for practical application in cutting-edge research fields such as new morphological computing, bio-electronic interface and electrocatalysis. For example, it can be used as a parent phase material to prepare low-valent nickel oxide compound RNiO2 crystals; in the field of new morphological computing, it can be used for neuromorphic computing, etc.; in the field of biology, it can be used to develop electrochemical biosensors; in the field of electrocatalysis, it can be used for electrochemical catalysts.
[0029] The beneficial effects of the present invention are as follows:
[0030] 1. At present, there are literature reports (Klein et al. Cryst. Growth Des. 21, 4230-4241 (2021)) that use chloride as a flux to grow RNiO3 crystals under 2000 bar oxygen pressure and 1000°C. In comparison, the present invention uses an alkali flux system for the first time: first, the growth temperature of RNiO3 (R = Pr-Dy) crystals is reduced to below 400°C; second, the oxygen pressure required for growth is reduced to below 300 bar, which greatly reduces the danger in the growth process and the requirements for equipment; third, on this basis, the crystal size is increased, and relatively larger RNiO3 crystals are obtained under lower conditions, and the crystal size can reach 45-60μm.
[0031] 2. The flux growth method used in the present invention requires easy conditions to be achieved, is easy to operate, and requires simple raw materials that are easy to purchase. A large-sized RNiO3 single crystal can be obtained within a growth period of 3-12 days. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 is a microscopic morphology of the NdNiO3 crystal prepared in Example 1;
[0033] Figure 2 is the XRD pattern of the NdNiO3 crystal prepared in Example 1;
[0034] Figure 3 is a microscopic morphology of the NdNiO3 crystal prepared in Example 2;
[0035] Figure 4 is the XRD pattern of the NdNiO3 crystal prepared in Example 2;
[0036] Figure 5 is a microscopic morphology of the NdNiO3 crystal prepared in Example 3;
[0037] Figure 6 is the XRD pattern of NdNiO3 crystal prepared in Example 3;
[0038] Figure 7 is a microscopic morphology of the NdNiO3 crystal prepared in Example 4;
[0039] Figure 8 is the XRD pattern of the NdNiO3 crystal prepared in Example 4;
[0040] Fig. 9 is a microscopic morphology of the NdNiO3 crystal prepared in Example 5;
[0041] Fig.10 is the XRD pattern of the NdNiO3 crystal prepared in Example 5;
[0042] Fig.11 is a microscopic morphology of the GdNiO3 crystal prepared in Example 6;
[0043] Fig.12 is the XRD pattern of the GdNiO3 crystal prepared in Example 6;
[0044] Fig.13 is a microscopic morphology of the SmNiO3 crystal prepared in Example 7;
[0045] Fig.14 is the XRD pattern of the SmNiO3 crystal prepared in Example 7;
[0046] Fig.15is a microscopic morphology of the DyNiO3 crystal prepared in Example 8;
[0047] Fig.16 is the XRD pattern of the DyNiO3 crystal prepared in Example 8;
[0048] Fig.17 This is the XRD pattern of the material prepared in Comparative Example 1. DETAILED DESCRIPTION
[0049] The present invention is further described below in conjunction with specific examples, but is not limited thereto. The flux ratios mentioned below are all molar ratios.
[0050] Example 1
[0051] NiO and Nd2O3 are prepared in a stoichiometric ratio, mixed evenly, and pressed into tablets. They are added to the flux system NaOH-KOH (NaOH: KOH = 1: 1). The mass ratio of NiO and Nd2O3 raw materials to flux is 0.15: 1. They are loaded into an alumina crucible with a volume of Φ40mm×60mm. The crucible is placed in a high-pressure furnace, filled with high-purity oxygen to make the O2 pressure = 2bar, heated to 400℃ to melt it, and the oxygen pressure in the furnace reaches 5bar. The temperature is fully kept, and the temperature is lowered to 170℃ at a cooling rate of 10℃ / h to make it spontaneously crystallize. During the heat preservation and cooling process, the oxygen pressure is maintained stable at 100bar+ / -10bar. The growth cycle is 3 days, and NdNiO3 microcrystals can be obtained.
[0052] Test the microstructure of NdNiO3 microcrystals, such as Figure 1 As shown. Figure 1 It can be seen that the crystal size of the obtained NdNiO3 microcrystals is 1-10μm.
[0053] Test the X-ray powder diffraction pattern of NdNiO3 microcrystals, such as Figure 2 As shown. Figure 2 It can be seen that it is consistent with the standard card (PDF#04-013-9190), indicating that the obtained is an orthorhombic NdNiO3 crystal.
[0054] Example 2
[0055] NiO and Nd2O3 are prepared in a stoichiometric ratio, mixed evenly, and pressed into tablets. They are added to the flux system NaOH-KOH (NaOH: KOH = 1: 1). The mass ratio of NiO and Nd2O3 raw materials to flux is 0.15: 1. They are loaded into an alumina crucible with a volume of Φ40mm×60mm. The crucible is placed in a high-pressure furnace, filled with high-purity oxygen to make the O2 pressure = 88bar, heated to 400℃ to melt it, and the oxygen pressure in the furnace reaches 200bar. The temperature is fully kept, and the temperature is lowered to 170℃ at a cooling rate of 10℃ / h to make it spontaneously crystallize. During the heat preservation and cooling process, the oxygen pressure is maintained at 200bar+ / -10bar. The growth cycle is 3 days, and NdNiO3 crystals can be obtained.
[0056] Test the microstructure of NdNiO3 crystals, such as Figure 3 As shown. Figure 3 It can be seen that the crystal size of the obtained NdNiO3 microcrystals is 10-20μm.
[0057] Test the X-ray powder diffraction pattern of NdNiO3 crystal, such as Figure 4 As shown. Figure 4 It can be seen that the X-ray powder diffraction pattern is consistent with the standard card (PDF#04-013-9190), indicating that the obtained is an orthorhombic NdNiO3 crystal.
[0058] Example 3
[0059] NiO and Nd2O3 are prepared in a stoichiometric ratio, mixed evenly, and pressed into tablets, added to the flux system NaOH-KOH (NaOH: KOH = 1: 1), the mass ratio of NiO and Nd2O3 raw materials to flux is 0.15: 1, and loaded into an alumina crucible with a volume of Φ40mm×60mm. The crucible is placed in a high-pressure furnace, filled with high-purity oxygen to make the O2 pressure = 102bar, heated to 400℃ to melt it, at which time the oxygen pressure in the furnace reaches 200bar, fully heat-insulated, cooled to 360℃, cooling rate 5℃ / h, heat-insulated for 2h, cooled to 260℃, cooling rate 1℃ / h, to make it spontaneously crystallize, and during the heat-insulating and cooling process, the oxygen pressure is maintained at 200bar+ / -10bar, and the growth cycle is 7 days to obtain NdNiO3 crystals.
[0060] Test the microstructure of NdNiO3 crystals, such as Figure 5 As shown. Figure 5 It can be seen that the crystal size of the obtained NdNiO3 microcrystals is 20-40μm.
[0061] Test the X-ray powder diffraction pattern of NdNiO3 crystal, such as Figure 6 As shown. Figure 6It can be seen that the X-ray powder diffraction pattern is consistent with the standard card (PDF#04-013-9190), indicating that the obtained is an orthorhombic NdNiO3 crystal.
[0062] Example 4
[0063] NiO and Nd2O3 are prepared in a stoichiometric ratio, mixed evenly and pressed into tablets, and added to a flux system NaOH-KOH (NaOH:KOH=0:1), with a mass ratio of NiO and Nd2O3 raw materials to flux of 0.15:2. The raw materials are loaded into a platinum crucible with a volume of Φ40mm×60mm, and a platinum wire is inserted to induce crystallization. The crucible is placed in a high-pressure furnace, and high-purity oxygen is filled in it so that the O2 pressure = 106bar. The temperature is raised to 400°C to melt it. At this time, the oxygen pressure in the furnace reaches 240bar. The furnace is fully heated and cooled to 360°C at a cooling rate of 5°C / h. The temperature is maintained for 2h, and the temperature is cooled to 260°C at a cooling rate of 1°C / h to allow spontaneous crystallization. During the heating and cooling process, the oxygen pressure is maintained at 240bar+ / -10bar. The growth cycle is 7 days, and NdNiO3 crystals can be obtained.
[0064] Test the microstructure of NdNiO3 crystals, such as Figure 7 As shown. Figure 7 It can be seen that the crystal size of the obtained NdNiO3 microcrystals is 30-40μm.
[0065] Test the X-ray powder diffraction pattern of NdNiO3 crystal, such as Figure 8 As shown. Figure 8 It can be seen that the X-ray powder diffraction pattern is consistent with the standard card (PDF#04-013-9190), indicating that the obtained is an orthorhombic NdNiO3 crystal.
[0066] Example 5
[0067] NiO and Nd2O3 are prepared in a stoichiometric ratio, mixed evenly and pressed into tablets, and added to a flux system NaOH-KOH (NaOH:KOH=0:1), with a mass ratio of NiO and Nd2O3 raw materials to flux of 0.15:2. The raw materials are loaded into a platinum crucible with a volume of Φ40mm×60mm, and a platinum wire is inserted to induce crystallization. The crucible is placed in a high-pressure furnace, and high-purity oxygen is filled in it to make the O2 pressure = 112bar. The temperature is raised to 400℃ to melt it. At this time, the oxygen pressure in the furnace reaches 260bar. The temperature is fully kept, and the temperature is lowered to 350℃ at a cooling rate of 2.5℃ / h. The temperature is kept for 2h, and the temperature is lowered to 250℃ at a cooling rate of 0.5℃ / h to make it spontaneously crystallize. During the heat preservation and cooling process, the oxygen pressure is maintained at 260bar+ / -10bar. The growth cycle is 12 days, and NdNiO3 crystals can be obtained.
[0068] Test the microstructure of NdNiO3 crystals, such as Fig. 9 As shown. Fig. 9 It can be seen that the crystal size of the obtained NdNiO3 microcrystals is 40-60μm.
[0069] Test the X-ray powder diffraction pattern of NdNiO3 crystal, such as Fig.10 As shown. Fig.10 It can be seen that the X-ray powder diffraction pattern is consistent with the standard card (PDF#04-013-9190), indicating that the obtained is an orthorhombic NdNiO3 crystal.
[0070] Example 6
[0071] NiO and Gd2O3 are prepared in a stoichiometric ratio, mixed evenly and pressed into tablets, and added to a flux system NaOH-KOH (NaOH: KOH=1:1), with a mass ratio of NiO and Gd2O3 raw materials to flux of 0.15:2. The raw materials are loaded into a platinum crucible with a volume of Φ40mm×60mm, and a platinum wire is inserted to induce crystallization. The crucible is placed in a high-pressure furnace, and high-purity oxygen is filled in so that PO2=112bar. The temperature is raised to 400°C to melt the crucible. At this time, the oxygen pressure in the furnace reaches 260bar. The furnace is fully heated and cooled to 350°C at a cooling rate of 2.5°C / h. The temperature is maintained for 2h, and the temperature is cooled to 250°C at a cooling rate of 0.5°C / h to allow spontaneous crystallization. During the heating and cooling process, the oxygen pressure is maintained at 260bar+ / -10bar. The growth cycle is 3 days, and GdNiO3 crystals can be obtained.
[0072] Test the microstructure of GdNiO3 crystals, such as Fig.11 As shown. Fig.11 It can be seen that the obtained GdNiO3 crystal size is 1-10μm.
[0073] Test the X-ray powder diffraction pattern of GdNiO3 crystal, such as Fig.12 As shown. Fig.12 It can be seen that the X-ray powder diffraction pattern is consistent with the standard card (PDF#01-089-7728), indicating that the obtained GdNiO3 crystal is an orthorhombic crystal.
[0074] Example 7
[0075] NiO and Sm2O3 are prepared in a stoichiometric ratio, mixed evenly and pressed into tablets, and added to a flux system NaOH-KOH (NaOH: KOH=1:1), with a mass ratio of NiO and Sm2O3 raw materials to flux of 0.15:2. The raw materials are loaded into a platinum crucible with a volume of Φ40mm×60mm, and the crucible is placed in a high-pressure furnace, filled with high-purity oxygen to make the O2 pressure = 114bar, and heated to 400°C to melt it. At this time, the oxygen pressure in the furnace reaches 270bar. The furnace is fully kept warm and cooled to 200°C at a cooling rate of 10°C / h to allow it to crystallize spontaneously. During the heat preservation and cooling process, the oxygen pressure is maintained at 270bar+ / -10bar. The growth cycle is 3 days, and SmNiO3 crystals can be obtained.
[0076] Test the microstructure of SmNiO3 crystals, such as Fig.13 As shown. Fig.13 It can be seen that the obtained SmNiO3 crystal size is 10-30μm.
[0077] Test the X-ray powder diffraction pattern of SmNiO3 crystal, such as Fig.14 As shown. Fig.14 It can be seen that the X-ray powder diffraction pattern is consistent with the standard card (PDF#01-071-5269), indicating that the obtained SmNiO3 crystal is of orthorhombic system.
[0078] Example 8
[0079] NiO and Dy2O3 are prepared in a stoichiometric ratio, mixed evenly and pressed into tablets, added into a flux system NaOH-KOH (NaOH: KOH=1:1), the mass ratio of NiO and Dy2O3 raw materials to flux is 0.15:2, loaded into a platinum crucible with a volume of Φ40mm×60mm, placed in a high-pressure furnace, filled with high-purity oxygen so that the O2 pressure = 101bar, heated to 500℃ to melt it, at which time the oxygen pressure in the furnace reaches 260bar, fully heat-insulated, cooled to 200℃, and cooled at a rate of 12℃ / h to allow it to spontaneously crystallize. During the heat-insulating and cooling process, the oxygen pressure is maintained at 260bar+ / -10bar. The growth cycle is 3 days, and DyNiO3 crystals can be obtained.
[0080] Test the microstructure of DyNiO3 crystals, such as Fig.15 As shown. Fig.15 It can be seen that the obtained DyNiO3 crystal size is 50-70μm.
[0081] Test the X-ray powder diffraction pattern of DyNiO3 crystals, such as Fig.16 As shown. Fig.16It can be seen that the X-ray powder diffraction pattern is consistent with the standard card (PDF#01-089-7495), indicating that the obtained DyNiO3 crystal is an orthorhombic crystal.
[0082] Comparative Example 1
[0083] There are currently literature reports (Klein et al. Cryst. Growth Des. 21, 4230-4241 (2021)) using chloride as a flux to grow RNiO3 crystals under 2000 bar oxygen pressure and 1000°C.
[0084] In this comparative example, NiO and Nd2O3 are prepared according to a stoichiometric ratio, mixed evenly and pressed into tablets, and added to a flux system LiCl-KCl (LiCl:KCl=6:4), the mass ratio of NiO and Nd2O3 raw materials to flux is 0.1:1, and they are loaded into an alumina crucible with a volume of Φ40mm×60mm. The crucible is placed in a high-pressure furnace, and high-purity oxygen is filled into it so that the O2 pressure = 97bar. The temperature is raised to 650℃ to melt it. At this time, the oxygen pressure in the furnace reaches 300bar. It is fully kept warm and cooled to 50℃ at a cooling rate of 10℃ / h. It spontaneously crystallizes. During the insulation and cooling process, the oxygen pressure is maintained at 300bar+ / -10bar. The growth cycle is 5 days to obtain the product.
[0085] The X-ray powder diffraction pattern of the test product is as follows: Fig.17 As shown. Fig.17 It can be seen that its X-ray powder diffraction spectrum shows that the product is NdClO, which means that NdNiO3 crystals are not obtained using the LiCl-KCl flux system at 650°C and 300 bar oxygen pressure.
Claims
1. A method for growing rare earth perovskite nickel oxide crystals by a high pressure flux method, comprising the following steps: Using NiO and R2O3 as raw materials, R is a rare earth element, and using an alkali flux system to fill with oxygen to grow crystals. First, the temperature is raised to 400-500°C to fully melt the raw materials, and then the temperature is lowered to the growth temperature to grow the crystals. The oxygen pressure range is 5-300 bar, and the growth temperature is 150-450°C. After the growth is completed, a rare earth perovskite nickel oxide compound RNiO3 crystal is obtained; R = Nd, Sm, Gd or Dy, and the alkali flux is one of NaOH and KOH or a mixture of the two.
2. The method for growing rare earth perovskite nickel oxide crystals by high pressure flux method according to claim 1, characterized in that: When the co-solvent is a NaOH-KOH mixed system, the molar ratio of NaOH-KOH is 1:
1.
3. The method for growing rare earth perovskite nickel oxide crystals by high pressure flux method according to claim 1, characterized in that: The mass ratio of the raw material to the flux is 0.15:(1-2).
4. The method for growing rare earth perovskite nickel oxide crystals by high pressure flux method according to claim 1, characterized in that: During the cooling process to the growth temperature, the cooling rate is 15-0.4℃ / h.
5. The method for growing rare earth perovskite nickel oxide crystals by high pressure flux method according to claim 1, characterized in that: The growth temperature is 170-360℃.
6. The method for growing rare earth perovskite nickel oxide crystals by high pressure flux method according to claim 1, characterized in that: The oxygen pressure range is 5-270bar.
7. The method for growing rare earth perovskite nickel oxide crystals by high pressure flux method according to claim 1, characterized in that: The growth period of RNiO3 crystals is 3-12 days.
8. The method for growing rare earth perovskite nickel oxide crystals by high pressure flux method according to claim 1, characterized in that: The steps include: (1) NiO, R2O3, R is a rare earth element, are mixed in a stoichiometric ratio, pressed into tablets, added into a prepared flux system, mixed evenly, and obtained a crystal growth material; The flux is: NaOH-KOH, wherein the molar ratio of NaOH to KOH is (0-1):1; The mass ratio of the raw material to the flux is 0.15:(1-2); (2) placing the crystal growth material obtained in step (1) into a platinum crucible, filling it with oxygen, adjusting the pressure, heating it to 400-500° C., maintaining the temperature to allow the raw material to fully melt, and then cooling it to allow the crystal to grow, thereby obtaining a rare earth perovskite nickel oxide RNiO3 crystal; The crystal growth temperature range is 170-400° C., the oxygen pressure range is 5-300 bar, and the cooling rate is 10-0.5° C. / h.